Exploring the Potential of Research–Practice Partnerships to Support State Education Leaders as Agents of Change - Hannah Goldstein; Hayley Weddle (AERA Open)
State education agencies have increasing influence over educational policy and practice, with responsibilities ranging from vision setting to monitoring compliance with accountability policy. Although state education agency leaders are well positioned to advance change, capacity building at this level of the education system has been traditionally limited. Research–practice partnerships (RPPs) represent a promising venue to support the ability of state leaders to facilitate educational change. In this qualitative study, we drew on semistructured interviews with state education agency leaders and observations of RPP meetings to examine the state-level structures that pose challenges to leaders’ efforts to make change and how participating in an RPP can support leaders in addressing these challenges. Findings reveal how RPP engagement supported state leaders with navigating complex organizational silos and bureaucratic processes by promoting relationship building and supporting the use of evidence-based resources. These insights may inform future research and capacity-building efforts at the state level of the education system.